Toward New Ecologically Relevant Markers of Health for Cetaceans - Derous, Davina; ten Doeschate, Mariel; Brownlow, Andrew C.; Davison, Nicholas J.; Lusseau, David (Frontiers in Marine Science, 2020)
Multiple stressors caused by human-induced disturbances can affect the foraging opportunities of cetaceans, potentially depleting their energy stores, and ultimately impact survival and reproductive success. Currently, blubber thickness and lipid composition is used as measure of health and nutritional status in cetaceans. This assumes that blubber functions in the same manner as adipose tissue in terrestrial mammals. However, cetaceans have evolved to have thickened blubber which serves as thermoregulation, buoyancy and energy store. In addition, blubber is composed of several layers and regions that have different physiological functions. We currently lack a clear understanding of how blubber biology contributes to maintaining energy status in cetaceans and several studies show blubber thickness, and composition in some body regions, is an inappropriate measure of health. Before new markers of health can be identified, we need to understand how environmental stressors influence blubber biology and particularly unravel its complex signalling roles with other organs. Currently, we do not understand how changes in energy status drive changes in health in cetaceans and eventually population dynamics. This review synthesises recent developments in cetacean blubber biology to propose potential directions to develop novel cetacean health markers.